Pola Asuh dan Depresi Pada Remaja - Ajeng Ardhya Ramadhanti (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2020)
Introduction: Depression is a mood-swing disorder that changes in a person within a certain period of time. Someone who suffers from depression will experience changes in mood, easily agitated, sensitive, feeling helpless, fatigue, decreased in concentration, changes in appetite, difficulty sleeping and symptoms of cramps, pain or indigestion without apparent cause. There are internal and external factors that caused depression in adolescents. Parenting is one of the environmental factors that influenced the mental condition of adolescents, which in turn can be an inhibiting factor or risk factor for depression. Purpose: to determine the effect of parenting on the incidence of depression in adolescents. Method: This article was created using the literature review method involving citations from books and journal articles published nationally and internationally. Results: Parenting affects depression in adolescents. Based on the three types of parenting such as democratic, permissive and authoritarian, it is known that democratic parenting is the pattern of parenting which has the most positive influence on the prevention of depression in adolescents. Discussion: Parenting is a way of parenting parents for children which includes support and care for children, which affects their future. Parenting is categorized as democratic, permissive, and authoritarian. Parenting affects the incidence of depression in adolescents that can be known based on the form of support, motivation, affection from parents to children so that it will affect mental health and can be a factor causing depression when entering adolescence. Conclusion: Parenting affects the incidence of depression in adolescents and can be a negative influence if not controlled as early as possible. Keywords: adolescent, depression, parenting.